Emotions and Strength of Will - Rioux, Catherine (Les ateliers de l'éthique / The Ethics Forum, 2024)
Emotions often lead to akrasia and practical irrationality but can also help us respond to our practical reasons for action. If we think there exists an important distinction between akrasia and weakness of will, how should we then rethink emotions’ contribution and threats to practical rationality? By drawing on recent work on willpower, I invite Tappolet to consider this question.